2014
DOI: 10.2500/ajra.2014.28.4032
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Rhinosinusitis with Nasal Polyps and without Nasal Polyps is Associated with Increased Expression of Lysophosphatidic Acid–Related Molecules

Abstract: LPA in human sinus mucosa may play important roles in the pathogenesis of CRS, contributing to produce CRS-related cytokines. LPA-related molecules were increased in CRS, which may attribute to CRS-related cytokines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Another pathway resulting in LPA production involves the hydrolysis of LPC via lysophospholipase D (also called autotaxin) [ 261 ]. Multiple studies suggest that both LPA concentration (specifically polyunsaturated species) and autotaxin levels and activity are increased in allergic diseases and asthma [ 67 , 261 , 262 , 263 ]. Moreover, serum autotaxin levels were found to correlate with pruritus in patients with atopic dermatitis [ 246 ].…”
Section: Phospholipase D Cleavage Product: Lysophosphatidic Acid (Lpa)mentioning
confidence: 99%
“…Another pathway resulting in LPA production involves the hydrolysis of LPC via lysophospholipase D (also called autotaxin) [ 261 ]. Multiple studies suggest that both LPA concentration (specifically polyunsaturated species) and autotaxin levels and activity are increased in allergic diseases and asthma [ 67 , 261 , 262 , 263 ]. Moreover, serum autotaxin levels were found to correlate with pruritus in patients with atopic dermatitis [ 246 ].…”
Section: Phospholipase D Cleavage Product: Lysophosphatidic Acid (Lpa)mentioning
confidence: 99%
“…Our study showed that SOCS1 protein levels were higher in CRSsNP patients than in CRSwNP patients and controls. The study by Park et al showed that SOCS1 and SOCS3 are also expressed in the nasal mucosa of healthy individuals, but in patients with CRSwNP and CRSsNP (both asthma and non-atopic groups), both mRNA and protein levels increased dramatically [ 22 ]. In another study by Hulse and colleagues in the US, the level of SOCS3 by western blotting was significantly reduced [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…25 Thymic stromal lymphopoietin (TSLP) and lysophosphatidic acid (LPA) have also been demonstrated to be higher in patients with eosinophilic CRSwNP and within CRSwNP and CRSsNP patients compared to control patients, respectively. 5,30 Mediator major basic protein (MBP), which can trigger the release of histamine, was found in one study to be elevated in 87% of CRSwNP patients versus only 4% of controls. 12 This observation was confirmed in another study that added that MBP was absent in the nasal mucus of patients with AR.…”
Section: Nasal Mucus Inflammatory Markers and Disease Severitymentioning
confidence: 99%